Tinjauan Konteks Situasi Desain Mural Sebagai Bahasa Visual “Dampak Polusi Kendaraan Pada Kesehatan masyarat” Analisis Halliday - Haryono Haryono; Qatrunnada Qatrunnada; Irfan Hidayat (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Murals are positioned as texts that communicate social messages through a combination of visual and symbolic, and act as a medium for environmental advocacy in public spaces. This study discusses the mural design with the theme "The Impact of Vehicle Pollution on Public Health" as a form of visual language analyzed through M.A.K. Halliday's systemic functional linguistic approach, especially in the aspect of the situational context consisting of field, tenor, and mode. This analysis shows that the mural field reflects environmental issues and their impact on public health. The participants in this study include artists as message makers and the wider community as audiences; while the mode relies on strong visual images, symbolic colors, and text elements to strengthen the message. The results of the study reveal that this mural design not only functions as an artistic expression, but also as a means to build effective social awareness through visual strategies. This study emphasizes that understanding the situational context of mural design is very important for interpreting the message conveyed more deeply and critically to society.